2021
DOI: 10.3390/ma14237451
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II) Perfluorinated Carboxylate Complexes with Small Aliphatic Amines as Universal Precursors for Nanomaterial Fabrication

Abstract: Copper(II) carboxylate compounds with ethylamine and isopropylamine of the general formula [Cu2(RNH2)2(µ-O2CRf)4], where R = Et, iPr, and Rf = CnF2n+1, n = 1–6, were characterised in the condensed and gas phases by electron impact mass spectrometry (EI MS), IR spectroscopy, and thermal analysis. A mass spectra analysis confirmed the presence of metallated species in the gas phase. Among the observed fragments, the pseudomolecular ions [Cu2(RNH2)2(µ-O2CRf)3]+ were found, which suggests the dimeric structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The temperature of the decomposition process onset changed between 313 K and 322 K (T i ), while the temperature of the final product formation was from 540 K to 550 K (T f ). The aforementioned ranges of T i and T f are narrow, in contrast to the previously described complexes with perfluorinated carboxylates: 19,20 TEM diffraction patterns and EDX spectra for the residues revealed that the decomposition product is metallic copper for the complexes (1-4). In the case of the compound (5), with a tertiary amine, a mixture of copper(I) and (II) oxides was identified (Fig.…”
Section: Thermal Analysismentioning
confidence: 69%
See 3 more Smart Citations
“…The temperature of the decomposition process onset changed between 313 K and 322 K (T i ), while the temperature of the final product formation was from 540 K to 550 K (T f ). The aforementioned ranges of T i and T f are narrow, in contrast to the previously described complexes with perfluorinated carboxylates: 19,20 TEM diffraction patterns and EDX spectra for the residues revealed that the decomposition product is metallic copper for the complexes (1-4). In the case of the compound (5), with a tertiary amine, a mixture of copper(I) and (II) oxides was identified (Fig.…”
Section: Thermal Analysismentioning
confidence: 69%
“…The aforementioned ranges of T i and T f are narrow, in contrast to the previously described complexes with perfluorinated carboxylates: [Cu 2 ( t BuNH 2 ) 2 (μ-O 2 CR f ) 4 ], [Cu 2 ( i PrNH 2 ) 2 (μ-O 2 CR f ) 4 ], and [Cu 2 (EtNH 2 ) 2 (μ-O 2 CR f ) 4 ] (R f = CF 3 , C 2 F 5 , C 3 F 7 , C 4 F 9 ). 19,20…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on metal carboxylates has always been due to their important roles not only in synthetic chemistry, with the essence of the labile coordination modes of the carboxylate group, with architectures of open and porous frameworks [1][2], but also with regard to biological activities [3-4] and physiological effects [5][6]. The carboxylate groups can adopt a wide range of bonding modes, including monodentate, symmetric and asymmetric chelating, and bidentate and monodentate bridging [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%